Chinese undergraduates’ English reading self-efficacy, intrinsic cognitive load, boredom, and performance: A moderated mediation model - Jiang, Chenjuan (Frontiers in Psychology, 2023)
Introduction Research findings from various academic domains have demonstrated that students’ self-efficacy (SE) influences their academic performance while limited studies have explored how foreign language reading SE influences reading performance. The purpose of this quantitative study was to explore the relationship between reading SE, intrinsic cognitive load (CL), boredom, and reading performance. Methods The participants were 272 English-as-a-foreign-language (EFL) learners at a comprehensive university in China, who attended a compulsory English course for improving their English reading and writing proficiency. Data were analyzed through SPSS and structural equation modeling (SEM). Results The result of the study provided support for the hypothesized relationships. Students’ English reading SE is positively related to their reading performance and negatively related to intrinsic CL. Their intrinsic CL during reading comprehension is negatively related to reading performance. Reading boredom is negatively related to reading SE and reading performance but positively related to CL. Furthermore, students’ CL mediates the relationship between reading SE and performance while the negative achievement emotion of boredom moderates the relationship between reading SE and CL. Discussion The research highlights the importance of cognitive and emotional factors in influencing the relationship between foreign language reading self-efficacy and reading performance. Implications for EFL teachers and researchers are discussed.